Sosialisasi Pemasaran Digital, Literasi Keuangan Dan Pelatihan Pembuatan Besek Tape Bagi UMKM Desa Kasiyan Kecamatan Puger,Jember - Mainatul Ilmi; Nely Supeni (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2022)
The impact of the COVID-19 pandemic is still being felt by MSMEs in Indonesia to this day. MSMEs need to survive in the midst of the crisis by encouraging MSMEs to adapt and transform following business trends that are currently developing. One of them is MSME fish basket craftsmen and fermented cassava (Tape) producers in Kasiyan Village, Puger District, Jember Regency who require knowledge and understanding of digital marketing and financial literacy, as well as product innovation training in the form of Besek Tape as a means of broadening their horizons so that MSMEs can develop their businesses and are ready to face business challenges in the future.